Diagnostic value of autologous serum skin test in chronic auto immune urticaria - A. R., Saleena Beevi; Kurien, George; Vineetha, Mary (International Journal of Research in Dermatology, 2017)
Background: Urticaria affects up to 20% of the population during their life time. Urticaria occurring on almost all days for more than 6 weeks is classified as chronic urticaria. Chronic urticaria is one of the most vexing management problems the dermatologists face. Chronic urticaria cases in which no etiology can be found are labelled chronic idiopathic urticarial (CIU). In most cases of idiopathic urticaria, autoimmunity may be the initiating factor- chronic autoimmune urticaria. Autologous serum skin test (ASST) is a simple and reliable method to detect autoimmune urticaria. Methods: Among patients with chronic idiopathic urticaria, ASST is done to detect ASST positivity and thereby chronic autoimmune urticaria. Patient’s serum is separated and 0.05 ml injected intradermally on left forearm. Normal saline is injected intradermally at least 5 cm away as control. Wheal and flare at serum site which is 1.5 mm more than that of control is taken as positive. Results were analyzed using Microsoft excel and Epi info7. Results: 49 patients were studied and 34 (69.4%) showed ASST positivity, which is an indicator of autoimmune urticaria. Moreover, it was seen that ASST positive patients had more episodes of urticaria per week, compared to ASST negative patients. Conclusions: ASST is a simple and reliable method to detect chronic autoimmune urticaria. ASST positive patients have more episodes of urticaria compared to ASST negative patients.